ETNOGRAFI KOMUNIKASI MENGENAI BAHASAN SERAPAN SUKU BAWEAN - Amelia Wulandari, (2023)
This research aims to discuss the communication patterns of the Bawean tribe's absorption language, knowing the characteristics of the speech community, speech procedures and speech events that occur on Bawean Island using ethnographic communication and sociolinguistic approaches. The method used is descriptive qualitative using primary and secondary data sources. The sampling technique was purposive sampling. Researchers used three stages of data analysis according to Creswell, namely description, analysis, and interpretation with data triangulation. The final result of this research shows that the pattern of communication of absorption language that occurs can be divided into three, namely communication patterns in the family, communication patterns in the community and communication patterns in traditional and religious rituals. The characteristics of the speech community in Bawean Island can be reflected by the existence of ethnic diversity, language diversity, familiarity and friendliness, strong religiosity and livelihoods as migrants. Furthermore, the manner of speech in the use of Bawean language has levels, namely Abhesa Alos, Abhesa, and Tak Abhesa with 6 vowels and 22 consonants. In addition, speech events that occur on Bawean Island can be seen from the molod tradition and Bawean arts such as Jibul, Dhungka, Mandiling, Samman and Kercengan.